2006
DOI: 10.1186/1471-2210-6-12
|View full text |Cite
|
Sign up to set email alerts
|

6-Shogaol reduced chronic inflammatory response in the knees of rats treated with complete Freund's adjuvant

Abstract: Background6-Shogaol is one of the major compounds in the ginger rhizome that may contribute to its anti-inflammatory properties. Confirmation of this contribution was sought in this study in Sprague- Dawley rats (200–250 g) treated with a single injection (0.5 ml of 1 mg/ml) of a commercial preparation of complete Freund's Adjuvant (CFA) to induce monoarthritis in the right knee over a period of 28 days. During this development of arthritis, each rat received a daily oral dose of either peanut oil (0.2 ml-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 28 publications
3
42
0
2
Order By: Relevance
“…28 Using an in vitro and in vivo model system, we found that a water extract of ginger inhibited production of inflammatory mediators. Gingerol and shogaol, which are typical ginger-derived components, have potent anti-inflammatory activity 29,30 and would be expected to have an anti-inflammatory effect in the skin. Keratinocyte defense mechanisms include attraction and activation of leukocytes and lymphocytes, activation of the immune system, and the ensuing effects that these have on blood flow, coagulation, the complement system, and epidermal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…28 Using an in vitro and in vivo model system, we found that a water extract of ginger inhibited production of inflammatory mediators. Gingerol and shogaol, which are typical ginger-derived components, have potent anti-inflammatory activity 29,30 and would be expected to have an anti-inflammatory effect in the skin. Keratinocyte defense mechanisms include attraction and activation of leukocytes and lymphocytes, activation of the immune system, and the ensuing effects that these have on blood flow, coagulation, the complement system, and epidermal cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In the Complete Freund's Adjuvant monoarthritic model, 6-shogaol reduced the inflammatory response and thereby protected the femoral cartilage from damage of the knee joint of rats (Levy et al, 2006). An experimental study was conducted among the senior citizens of Hong Kong for moderate-to-severe knee pain by aroma-massage therapy with aromatic ginger and orange essential oil over a three week period (Yin et al, 2008) and found that the aroma-massage therapy seems to have potential as an alternative method for short-term knee pain relief.…”
Section: Effect Of Ginger On Knee Jointmentioning
confidence: 97%
“…Shogaols have been actively investigated in numerous studies, of which the majority has been conducted on 6-shogaol. In vitro and in vivo findings have indicated that 6-shogaol exerts anti-inflammatory effects [12,13]. Recently, our laboratory and Weng et al have reported the in vitro anti-invasive effects of 6-shogaol against breast carcinoma and hepatocarcinoma cells respectively [14,15].…”
Section: Introductionmentioning
confidence: 93%